Leadership Communication Conception of Malaysian Hindus and its Relevancy to Mahathir s Leadership - Suppiah, S Maartandan a/l; Ahmad, Dr. Mohd. Khairie; Yusof, Assoc. Prof. Dr. Norhafezah (Universitas Semarang, 2019)
Literatures proposed that culture does influence the success of leadership communication. Mahathir was criticised to be a leader who promotes the betterment of the majority community and marginalised the Indians. Despite of that, the Indians in Malaysia showed advancement in various sectors including politics, economy and social. Therefore, this exploratory study aims to bridge the gap by investigating the attributes that link between Mahathir s leadership communication and Indian community. Qualitative methodology was utilized and data were collected through a series of intensive interviews with 15 informants consists of Indian political, non-governmental organisation and community representatives. Based on the thematic analysis, two main attributes that strongly link to Indian culture were identified: leadership communication conception (Sattva Guna) and characteristics of good leadership communication (Sattva characteristics). This study has contributed to enhance understanding of leadership communication from multi-cultural context, specifically about the Indian s cultural conceptions.